Analisis Penetapan Hukum Keabsahan Menikahi Wanita Hamil Diluar Nikah Dalam Madzab Syafi’i - Ulfa, Hidayatun; Walyadi , Walyadi; Baehaqi, Muh. (El-Qenon: Journal of Islamic Law, 2024)
Various factors contribute to these pregnancies and marriages, including weak faith, free social interactions, and the desire to cover up disgrace, among others. This study aims to understand the legal status of marriages involving pregnant women out of wedlock according to the thoughts of Imam Syafi’i, as well as the methods used by Imam Syafi’i for legal application or istinbat. This type of research uses qualitative methods. Data collection techniques involve a library research approach, which means gathering data by reading books, journals, or other sources relevant to the discussion object. The data analysis technique used is qualitative descriptive, which describes or illustrates the object being studied through the collected data, from which conclusions can then be drawn. The results of this research indicate that, according to Imam Syafi’i, marriages involving pregnant women out of wedlock are considered valid. The marriage can take place when a woman is pregnant, whether the marriage is with the man who impregnated her or another man. Regarding the issue of iddah (waiting period), Imam Syafi’i opines that there is no iddah for pregnant women out of wedlock, with the aim of preserving the purity of lineage for the child born as a result of the extramarital relationship (zina). Imam Syafi’i’s opinion is largely referenced by the Compilation of Islamic Law (KHI), although there are differences. The fundamental benefit of legitimizing the marriage of pregnant women out of wedlock is based on maslahah dharuriyah, which includes the fundamental aspects of welfare for the preservation of religion, life, intellect, lineage, and property.